2022
DOI: 10.1134/s0006350922060197
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationship between Physiological and Pathological Processes in the Brain and in the Gastrointestinal Tract: The Brain–Intestine Axis

Abstract: The brain and gastrointestinal tract are the most important organs responsible for detecting, transmitting, integrating, and responding to signals coming from the internal and external environment. A bidirectional system of neurohumoral communication (the "intestine-brain" axis) combines the activity of the intestine and brain (or brain and intestine) of a person. It affects human development and behavior. This paper analyzes the literature data on the existence of a relationship between the central and entera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…В настоящее время установлена взаимосвязь ВЗК с развитием нарушений в головном мозге [28]. Показано развитие депрессивных состояний при ВЗК у больных, а также нарушение их когнитивных функций при повреждении желудочно-кишечного тракта [29,30].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…В настоящее время установлена взаимосвязь ВЗК с развитием нарушений в головном мозге [28]. Показано развитие депрессивных состояний при ВЗК у больных, а также нарушение их когнитивных функций при повреждении желудочно-кишечного тракта [29,30].…”
Section: Discussionunclassified
“…Показано развитие депрессивных состояний при ВЗК у больных, а также нарушение их когнитивных функций при повреждении желудочно-кишечного тракта [29,30]. Эти данные, наряду с установленным нами увеличением концентрации 3-НТ в крови у детей с ВЗК, являются основанием для предположения о вовлечении в патогенез ВЗК рецепторов глутамата, которые обеспечивают взаимосвязь кишечник-мозг при этих аутоиммунных воспалительных заболеваниях [28]. Проведённый нами ранее анализ содержания аутоантител к GluRc показал, что у большинства детей с ЯК и БК уровень аутоантител к NMDA GluRc значительно превышает нормальные значения для здоровых детей.…”
Section: Discussionunclassified
“…Intestinal tract is known as the ‘ second brain ‘ of human beings. The metabolism of intestinal flora has important feedback-and-regulation effects on the physiological functions of the body ( Reutov and Sorokina, 2022 ). Research has demonstrated that metformin can ameliorate the metabolic and endocrine profiles of PCOS patients, as well as the diversity and abundance of intestinal flora ( Gan et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%